2012
DOI: 10.1111/j.1440-1754.2012.02449.x
|View full text |Cite
|
Sign up to set email alerts
|

Contamination rates of different urine collection methods for the diagnosis of urinary tract infections in young children: An observational cohort study

Abstract: Contamination rates in CCU are much higher than in CSU and SPA samples. Ideally, SPA should be used for microbiological assessment of urine in young children. Collection procedures need to be optimised if CCU is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
3
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 26 publications
11
110
3
8
Order By: Relevance
“…Contamination rates have been shown to vary from 0% in clean-catch urine of 23 samples to 48% of bag urines. 98 In a retrospective observational cohort study, contamination in clean catch, catheter specimen of urine and bag was 1%, 12% and 26%. 98 Definitions of contamination vary from single organism growth < 10 5 OR ≥ 2 organisms to ≥ 2 organisms present at > 10 5 CFU/ml of urine.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Contamination rates have been shown to vary from 0% in clean-catch urine of 23 samples to 48% of bag urines. 98 In a retrospective observational cohort study, contamination in clean catch, catheter specimen of urine and bag was 1%, 12% and 26%. 98 Definitions of contamination vary from single organism growth < 10 5 OR ≥ 2 organisms to ≥ 2 organisms present at > 10 5 CFU/ml of urine.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…98 In a retrospective observational cohort study, contamination in clean catch, catheter specimen of urine and bag was 1%, 12% and 26%. 98 Definitions of contamination vary from single organism growth < 10 5 OR ≥ 2 organisms to ≥ 2 organisms present at > 10 5 CFU/ml of urine. In a US study, no institutional factors, such as access to refrigeration, were found to associate with either low or high contamination rates.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Otro estudio, que comparó los diferentes métodos de recogida de muestra de orina en niños menores de dos años, asocia la recogida mediante acecho con un índice de contaminación del 26%, significativamente mayor que aquellas recogidas por sondaje (12%) o punción suprapúbica (1%). Relacionan el elevado porcentaje de contaminación en la primera técnica citada con la falta de estándares de recogida, y recomiendan nuevos estudios, dada la alta variabilidad de tasas de contaminación en la bibliografía 11 . En nuestra experiencia, las cifras de contaminación en las muestras recogidas mediante el acecho y aquellas por sondaje vesical fueron similares, por lo que podemos considerar el acecho como una técni-ca válida para la obtención de muestras de orina.…”
Section: Discussionunclassified
“…Two recent studies, carried out in a hospital setting, evaluated the preferred methods of urine collection for UTI diagnosis in children in two different pediatric departments, one in Turkey [ 13 ], which reported a population aged 0-16 years, and the other in Australia [ 14 ], which looked at a population younger than 2 years of age. In the Turkish study, considering only the subjects aged 2 years and under (532), the sterile bag was the most frequently used method and was used in 90 % of cases, followed by clean catch in 7 %.…”
Section: Urine Collectionmentioning
confidence: 99%